Capital Budgeting Practices in Nepali Manufacturing Companies - Dangol, Jeetendra; Sthapit, Arhan; Rajbhandari, Rameshwor (PYC Nepal Journal of Management, 2011)
The paper analyses the capital budgeting (CB) techniques and other related practices of Nepali manufacturing companies. Based on the survey conducted in the month of September 2010 in the Kathmandu Valley through a structured questionnaire, the study assessed different aspects of the capital budgeting practices of 40 Nepali manufacturing companies. On the basis of analysis, the study found that CB decisions are largely centralised to the higher rungs of the organisation. It has also shown the Nepali companies shifting towards the increased use of sophisticated, discounted model for the capital budgeting evaluation.